Examining the measurement invariance of the teachers' sense of self-efficacy scale in terms of gender - Yıldız Burcu Doğan; Huseyin Akar; Mehmet Üstüner (Institute of Advanced Engineering and Science, 2019)
The aim of this research was to analyze the measurement invariance of the